Moxonidine for tramadol withdrawal symptoms during detoxification. (8th July 2015) - Talih, Farid; Ghossoub, Elias
Abstract : It is well documented in the literature that noradrenergic pathways are key in the manifestation of opioid withdrawal symptoms, which is why clonidine is used as an off-label agent in opioid detoxification regimens given its anti-sympathetic properties. Moxonidine is a selective I1-imidazoline receptor agonist, similar to clonidine but with no α2-adrenergic agonist activity and subsequently fewer side effects. We report the case of a 33-year-old woman with a 15-year history of tramadol use who was admitted voluntarily for detoxification. She was started on moxonidine and had an uneventful detoxification. Two months after discharge, the patient maintained tramadol abstinence with good tolerability to moxonidine. To the best of our knowledge, this has not been previously reported in the medical literature.